Association between eating habits, sweet taste assessment, and high-sugar food consumption among elementary school students in Daegu: a descriptive study - Min-Jung Kim; Eun-Kyung Shin; Yeon-Kyung Lee (Korean Journal of Community Nutrition, 2023)
Objectives: The purpose of this study was to analyze high-sugar food consumption habits frequency among elementary school students, and their correlations with eating habits and sweet taste assessment.